Digitalisasi Sistem Pembayaran Dan Dampaknya Terhadap Inklusi Keuangan Di Indonesia - Fadhilah (CV. SINAR HOWUHOWU, 2025)
The digitalization of payment systems has become a key factor in promoting financial inclusion in Indonesia. This study aims to analyze the impact of digital payment services on the access and participation of the public in the formal financial system. A quantitative approach was employed, collecting data through surveys of 400 respondents across urban and rural areas. Data analysis was conducted using multiple linear regression to examine the relationship between payment digitalization and financial inclusion, complemented by in-depth interviews for contextual understanding. The results indicate that digital payment systems significantly enhance financial inclusion; however, challenges such as uneven digital literacy, infrastructure limitations, and concerns over transaction security remain. The study recommends improving digital education, developing technological infrastructure, and implementing stringent security policies to broaden inclusive and sustainable financial inclusion in Indonesia.